Design Of The Inventory Application Using The Laravel Framework Based On PT. Nelson Mandiri Sukses Abadi - Hindri Widyawati; Syaifudin; Teddy Siswanto (Penerbitan Universitas Trisakti, 2022)
The purpose of this study is to develop an inventory application for PT. Nelson Mandiri Sukses Abadi because the warehouse division still records data recaps manually in books, which can be time consuming and prone to errors. PT. Nelson Mandiri Sukses Abadi provided the data in the form of a Microsoft Excel file. The waterfall method was used to collect the necessary data and get to the stage of making the application and the programming language used was PHP and the database was MySQL using the Laravel Framework. Based on the data analysis results, it can be concluded that PT. Nelson Mandiri Sukses Abadi requires an application as a support for recording goods every day, tracking records of goods entering and leaving the warehouse and presenting reports in order to improve performance quality.